The Influence of Service Quality and Non-Performing Loans On Customer Satisfaction at BPR Eka Dana Mandiri, Malang City - Yasinta Mei; Cakti Indra Gunawan; Willy Tri Hardianto (IRDH International Journal of Social Sciences & Humanities, 2026)
Rural Banks (BPRs) are financial institutions that play an important role in supporting communities by providing credit, particularly to small and medium-sized enterprise (SME) entrepreneurs. This study aims to examine the effects of service quality and non-performing loans on customer satisfaction at BPR Eka Dana Mandiri in Malang City. The research employs multiple linear regression analysis. Data were collected through questionnaires distributed to customers and analyzed using quantitative associative methods. Based on responses from 89 respondents, the results indicate that good, friendly, and professional service significantly increases customer satisfaction. In contrast, non-performing loans have a negative and significant effect on customer satisfaction. Simultaneously, service quality and non-performing loans influence customer satisfaction, with a contribution of 30.6%